Large outbreak of food poisoning caused by Salmonella typhimurium definitive type 49 in mayonnaise. Issue 6666 (14th January 1989) - Mitchell, E.; O'Mahony, M.; Lynch, D.; Ward, L. R.; Rowe, B.; Uttley, A.; Rogers, T.; Cunningham, D. G.; Watson, R.
Abstract : An investigation was conducted to determine the vehicle of infection of an outbreak of food poisoning in a large metropolitan building early in 1988. A questionnaire was distributed to 700 people who had eaten in the building during the week of the outbreak, and attack rates for specific food were calculated. Food and stool samples, environmental samples, and eggs and environmental swabs from the egg suppliers were examined microbiologically. Altogether 474 questionnaires were returned, 120 people reporting gastrointestinal illness. The illness was significantly associated with foods containing mayonnaise. Salmonella typhimurium definitive type 49 was isolated from 76 of the 84 stool samples containing salmonella and from five of the eight samples taken from the chicken house of the main egg supplier. Mayonnaise was probably the vehicle of infection, which was caused by S typhimurium definitive type 49.